Learning Speaking Through Podcast For FLDP Students Of English Department At IAIN Madura - Firdausiyah, Firdausiyah; Rohaniyah, Jaftiyatur (International Journal of English Education and Linguistics (IJoEEL), 2024)
This study investigates the use of podcasts as a teaching media for developing speaking skills among FLDP students, FLDP is foreign Language Development Program which is provided for a fresh students at IAIN Madura. There are some specific topic as: self introduction, My Family, My Hobby, My Job, and My Campus as the theme of podcast. Podcast provides a flexible platform that promotes fluency, accuracy, and communicative competence. The research problem focusing on identifying how podcast tasks enhance speaking skills. A qualitative study approach was taken as the research method, with data collected through observation and documentation. Twenty five students were divided into several groups. The data were analyzed using Miles and Huberman's model, which includes data reduction, data display, and conclusion drawing. The findings indicate that podcasts not only enhance students' speaking abilities but also foster engagement and confidence in language use. It suggests that podcasts can be a valuable tool for EFL classrooms. In conclusion, Incorporating podcasts into EFL classrooms appears to be a promising method for improving speaking skills and fostering a positive learning environment.